Improving Understanding of The Concept of Multiple with Manipulative Objects through A Realistic Approach in Class II Elementary School Students - Nurafiyah Nurafiyah (Green Publisher Indonesia, 2023)
Mathematics subjects in grade II SDN Pondok Aren 04, Pondok Aren District, South Tangerang City, can be seen as quite preferred subjects by students. Student activity in learning mathematics is quite good, although the desired results have not been maximized. The objectives of the research are; (1) to find out whether students' understanding of multiplication using a realistic approach grade II SDN Pondok Aren 04 Pondok Aren District, South Tangerang City, Antapani District increased?, and (2) to find out whether students' interest in teaching mathematics in grade II multiplication is better?. The method used in this study is an analytical descriptive method with a class action model. The results obtained from the study are (1) learning mathematics using a realistic approach can increase students' understanding in multiplication. It can be seen from the results obtained by students in mathematics learning there is an improvement, and (2) student attitudes in learning mathematics using a realistic approach can increase student interest in mathematics, so that mathematics is no longer a difficult subject to understand and understand.